Analysis of The Impact of Early Marriage and Prevention Efforts in Sedau Village - Faturahman, Sidik; Husen, Wan Ridwan (AbdimasMu UMTAS, 2023)
Early marriage among teenagers in Sedau Village is so concerning. This study aims to describe one of the problems found in the community in Sedau village, Narmada sub-district, West Lombok, West Nusa Tenggara, namely the high rate of early marriage. The limitations of this research problem include the impact of early marriage and prevention efforts. This research is included in the descriptive qualitative research with the type of case study research. The results obtained from interviews with the village head of Janapria and the community stated that many community members married underage. The highest number of early marriages in Sedau village is found in 3 hamlets. Various impacts that occur as a result of early marriage for young couples include health for mothers and babies, economic and social, educational, psychological, and legal. As for prevention efforts by conducting outreach to adolescents, outreach to the community or parents who have teenage children, as well as increasing the participation of official institutions in Janapria to assist in preventing or minimizing early marriage.